Biocontainment strategies for in vivo applications of Saccharomyces boulardii - Hedin, Karl Alex; Kruse, Vibeke; Vazquez-Uribe, Ruben; Sommer, Morten Otto Alexander (Frontiers in Bioengineering and Biotechnology, 2023)
The human gastrointestinal tract is a complex and dynamic environment, playing a crucial role in human health. Microorganisms engineered to express a therapeutic activity have emerged as a novel modality to manage numerous diseases. Such advanced microbiome therapeutics (AMTs) must be contained within the treated individual. Hence safe and robust biocontainment strategies are required to prevent the proliferation of microbes outside the treated individual. Here we present the first biocontainment strategy for a probiotic yeast, demonstrating a multi-layered strategy combining an auxotrophic and environmental-sensitive strategy. We knocked out the genes THI6 and BTS1, causing thiamine auxotrophy and increased sensitivity to cold, respectively. The biocontained Saccharomyces boulardii was unable to grow in the absence of thiamine above 1 ng/mL and exhibited a severe growth defect at temperatures below 20°C. The biocontained strain was well tolerated and viable in mice and demonstrated equal efficiency in peptide production as the ancestral non-biocontained strain. In combination, the data support that thi6∆ and bts1∆ enable biocontainment of S. boulardii, which could be a relevant chassis for future yeast-based AMTs.